How degradation of calcium phosphate bone substitute materials is influenced by phase composition and porosity - Schaefer, S.; Detsch, Rainer; Uhl, Franziska Elisabeth; Deisinger, U.; Ziegler, G. (Advanced Engineering Materials, 2011)
The chemical composition of calcium phosphate (CaP) materials for the regenerative therapy of large bone defects is similar to that of bone. Additionally, calcium phosphates show an excellent biocompatibility. Besides the support of defect healing calcium phosphate implants should be completely degraded within an adequate time period to be replaced by newly formed bone. Although degradation of CaP-implants occurs mainly by dissolution of the material, it is important to characterize the osteoclastic resorption as well, which is involved in native bone remodeling. The degradation of bone substitutes made of calcium phosphate ceramics is influenced by various parameters, such as defect size and localization, the general health situation, and age of the patient, but also material properties are important. Especially, the calcium phosphate composition is crucial for the degradation behavior of a calcium phosphate material. Additionally, at the cellular level the micro- and macroporosity, including interconnecting pores, influences both, the dissolution and the osteoclastic resorption. In our study, three different calcium phosphate materials (hydroxyapatite, tricalcium phosphate, and a biphasic calcium phosphate) and two different geometries (dense 2D samples and porous 3D scaffolds) are compared regarding their dissolution and resorption behavior. The results show, that the dissolution of CaP-ceramics, as examined by the incubation in a degradation solution, depends mainly on the calcium phosphate phase but also on the porosity of the implant. Regarding the resorption, cell proliferation and differentiation of a monocytic cell line as well as the formation of resorption lacunas are analyzed. Cell proliferation is comparable on all phase compositions. Cell differentiation and resorption, however, are influenced by the calcium phosphate phase composition and by the implant porosity as well. By understanding these two mechanisms of degradation, bone substitute materials and, as a result, the bone regeneration of large bone defects using CaP-ceramics can be improved. Degradation of synthetic calcium phosphates that are used for bone substitution is defined by both chemical dissolution (physicochemical degradation) and resorption (cellular degradation by osteoclasts). In summary, the degradation mechanisms depend on both, the calcium phosphate composition and the sample micro- and macroporosity. Therefore, degradation of a bone substitute can be adjusted in the individual case by both parameters, whereby phase composition has a greater influence than sample porosity. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGa